Perspective of Parents of Infants and Children with Hearing Impairment about Hearing Aid Management: A Questionnaire-Based Study - Kumar, Anil; Bhat, Rashmi J. (International Archives of Otorhinolaryngology, 2025)
It is important to understand the intricacies of hearing aid management early in the child's life to appreciate the full benefits of early intervention.Identifying aspects of hearing aid management that carers regard as taxing will allow hearing professionals to focus and encourage these areas, potentially leading to higher hearing aid use and better outcomes.49 parents of children with hearing impairment participated in the study. Parent Hearing Aid Management Inventory (PHAMI) was used to explore parent access to information and experiences in three domains such as parent skills and confidence in hearing aid management, hearing aid use, and communication with the audiologist using a 4-point rating scale. The data was collected using direct interviews and through Microsoft forms.The majority of the parents desired information and support in identifying hearing aid options/accessories, obtaining financial assistance for costs, and using a listening stethoscope for determining when the hearing aid was not working. The most common challenges identified by parents as influencing their child's hearing aid use were activities (for example, playing, travelling in the car), and the fear of losing and damaging the hearing aids. Although many parents were pleased with the audiologist's assistance, they desired that the audiologist be more patient and contact them more regularly after the hearing aids were fitted.Professionals can help with effective device management by addressing parental challenges, collaborating on specific device management goals, and helping as needed.
Keywords: hearing aid management; parent perspective; outcomes; pediatric audiology